Tramas de las desigualdades: mujeres rurales en la educación superior universitaria, Salta Argentina - Gonzalo Víctor Humberto Soriano; María Macarena Ossola (Universidade Federal do Norte do Tocantins, 2022)
This article presents the analysis of the various social positions occupied by young women who move from their place of origin in the rural context (San Carlos, Salta, Argentina) to the capital of the province to study at the National University of Salta (UNSa). We take into account that this group of young women goes through different experiences in the university institution, in which they are questioned based on their social, age, rural and gender conditions. Such experiences make up a field of multiple meanings in which cultural diversity, the effort to achieve an academic degree, as well as historical relations of inequality intermingle.